Developing a new modification technology of oat flour based on differential pressure explosion puffing. (April 2021) - Zhang, Yifu; Chen, Cheng; Wang, Nan; Chen, Yue; Yu, Jiaojiao; Zheng, Xuechao; Li, Shuhong; Chen, Ye
Abstract: This research developed differential pressure explosion puffing (DPEP) technology to modify oat. The effects of heating time, puffing temperature and differential pressure on gelatinization degree, water absorption, solubility, thermodynamics properties, gelatinization properties and crystal structure of oat flour were investigated. The gelatinization degree of starch in oats treated with DPEP was 99.73 g/100 g, and the solubility and water absorption of modified oat flour increased to 3.90 g/100 g and 2.81 g/g, respectively. Thermodynamic properties indicated that the gelatinization temperature and enthalpy of the modified oat flour decreased to 58.19 °C and 0.06 J/g respectively. The peak viscosity, trough viscosity and final viscosity of modified oat flour increased to 2.20 Pa s, 1.77 Pa s and 3.55 Pa s, respectively, oat flour had lower disintegration value and higher shear resistance. However, under long-term high temperature treatment, starch and lipid formed complex, leading to gradual transformation of the crystal structure from A-type to V-type, and water absorption, solubility and viscosity decreased. Highlights: Modified flour had higher gelatinization degree and lower gelatinization temperature. Oat starch was gelatinized and partially decomposed after modification treatment. The starch lipid complex was formed in long time and high temperature treatment.